2010
DOI: 10.1007/s00442-010-1775-1
|View full text |Cite
|
Sign up to set email alerts
|

Earthworms, as ecosystem engineers, influence multiple aspects of a salamander’s ecology

Abstract: Ecosystem engineers create habitat that can be used by other species in multiple ways, such as refugees from predators, places to breed, or areas with increased prey resources. I conducted a series of enclosure experiments to: (1) determine if salamanders use earthworm burrows, and (2) examine the potential influence of earthworm burrow use and indirect effects on salamander intra- and interspecific competition, predator avoidance, and seasonal performance. I found that one species of woodland salamander, Plet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 28 publications
0
28
1
Order By: Relevance
“…The presence of earthworms can further complicate the relationship of salamanders and litter decomposition. Adult nightcrawlers ( Lumbricus terrestris ) burrows provide refuge for red-backed salamanders from extreme temperatures and predators, but reduce leaf litter and microarthropod abundance [56]. Juvenile nightcrawlers can be an important prey source for salamanders [56].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of earthworms can further complicate the relationship of salamanders and litter decomposition. Adult nightcrawlers ( Lumbricus terrestris ) burrows provide refuge for red-backed salamanders from extreme temperatures and predators, but reduce leaf litter and microarthropod abundance [56]. Juvenile nightcrawlers can be an important prey source for salamanders [56].…”
Section: Discussionmentioning
confidence: 99%
“…Adult nightcrawlers ( Lumbricus terrestris ) burrows provide refuge for red-backed salamanders from extreme temperatures and predators, but reduce leaf litter and microarthropod abundance [56]. Juvenile nightcrawlers can be an important prey source for salamanders [56]. In small enclosures, the consumption of juvenile earthworms by adult salamanders reduced the rate of litter decomposition, but the presence of adult earthworms overwhelmed any effect of salamanders by breaking down nearly all leave litter [57].…”
Section: Discussionmentioning
confidence: 99%
“…Literature regarding the effects of invasive earthworms on salamanders is scarce, but recent investigations into the behavioural interactions between invasive earthworms and the Eastern Red-backed Salamander (Plethodon cinereus (Green, 1818)) have focused on the role of the deep-burrowing, European nightcrawler (Lumbricus terrestris L., 1758) as an ecosystem engineer (Cáceres-Charneco and Ransom 2010;Ransom 2011Ransom , 2012aRansom , 2012b. Ransom (2011Ransom ( , 2012b showed that salamander fossorial activity is influenced by the presence of earthworm burrows and demonstrated potential benefits of invasive earthworm burrows for salamanders, including bolstering overwintering success and serving as refugia from predators. Also, there is evidence that salamander behavioural responses to invasive earthworms can be learned within a single generation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, seeds may be affected by direct consumption, while seedlings may be affected by desiccation of fine roots after leaf litter disappearance [9]. In addition, earthworm relative abundance and their associated impacts are also affected by land use history and grazing regimes [17], facilitation between earthworms and non-native plant species [7], and alterations of predator–prey interactions [6,18]. Furthermore, earthworms and abundant white-tailed deer ( Odocoileus virginiana Zimmermann) in North America may interact and affect plants in multiple yet poorly understood ways.…”
Section: Introductionmentioning
confidence: 99%